Searching for Ethics: Legal Requirements and Empirical Issues for Anthropology - Perrin, Julie; Bühler, Nolwenn; Berthod, Marc-Antoine; Forney, Jérémie; Kradolfer Morales, Sabine; Ossipow-Wuest, Laurence (Swiss Journal of Sociocultural Anthropology, 2020)
This document is a translation of the 2018 article «Searching for Ethics: Legal requirements and empirical issues for anthropology» (Perrin et al. 2018). It analyses the new legal provisions impacting qualitative research practices and contributing to the institutionalization of research ethics in social sciences and the humanities in Switzerland. After contextualizing the emergence of new forms of research regulation, it shows how their epistemological assumptions challenge anthropology. It then explores the issues related to the articulation between procedural ethics and processual ethics. Finally, it discusses the different postures which might possibly be adopted by scholars in anthropology and other qualitative social sciences.